Synergetic effect of UiO-66 and plasmonic AgNPs on PET waste support towards degradation of nerve agent simulant; Chemical Engineering Journal; Vol. 431 - Semyonov O. V. Oleg Vladimirovich; Kogolev D. A. Dmitry Anatoljevich; Mamontov G. V. Grigory Vladimirovich; Kolobova E. N. Ekaterina Nikolaevna; Trelin A. Andrey; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich (2022, 2022)
Title screen